A fast and highly sensitive method for the detection of canine distemper virus by the naked eye - Basso, Caroline Rodrigues [UNESP]; Tozato, Claudia de Camargo [UNESP]; Araújo Junior, João Pessoa [UNESP]; Pedrosa, Valber de Albuquerque [UNESP] (Royal Soc Chemistry, 2015)
An easy, low cost method for the detection of canine distemper virus (CDV) that requires no instrumentation and uses gold nanoparticle-labeled antibodies is presented. The proposed method shows a linear relationship between the concentration and signal in the range of 0 to 1.5 mu g L-1 with a detection limit of 0.7 ng mL(-1). The method was successfully applied to the detection of CDV in real samples of urine and the results from these studies correlate with values obtained using conventional methods. Our results offer the possibility of easy, rapid and reliable clinical diagnosis of CDV by monitoring the colorimetric changes and measuring linear surface plasmon resonance (LSPR) changes in urine samples. The rapid visual detection of the virus using a test assay may offer a simple and cost-effective alternative to highly complex and instrument-dependent commercial methods.